PENGUJIAN MODEL PENERIMAAN TEKNOLOGI INTERNET PADA MAHASISWA - Mega Wijaya, Petra Surya (Fakultas Bisnis UKDW, 2005)
The rapid growth of investment in information technologt by orgoniza tions worldwide has made user acceptance an increasingly criticol technologt implementation and *orogr*rnt issues. User